EFFECTS OF ADMIXTURES ON THE CRYSTALLISATION RATE OF GYPSUM A BATCH CRYSTALLISATION STUDY - S. Muryanto; H. M. Ang (Reaktor, 2004)
This paper descripbes a study on the effects of admixtures on the crystallization rate of gypsum. Two different types of biodegradable admixtures commonly used as flotation agent in copper/zinc concentrate production, namely, sodium isopropyl xanthate (=SIPX) and isopropyl thionocarbamate were investigated in this study. A laboratory batch crystallizer was used in this study, and the experiments were run using seeded method. The rate of desupersaturation or the time required to reach the equilibrium concentration was  compared for varying admixture oncentrations. It was discovered that the added seed crystals started growing imediately upon addition into the supersaturated solution, i.e. there  was no induction time.Results of this batch crystallizationstudy suggest that addition of admixtures individually or in combination, significantly affects the crystallization kinetics and in particular, reduces the rate of crystallization of gypsum. Activation energies were determined using three different temperatures, and the values obtained  mostly agreed with other published values, i.e. 60.00 ± 3.00, 57.39 ± 2.87, and 37.65 ±1.88 kj/mol, for pure gypsum, isopropyl yhionocarbamate, and SIPX, respectively.Keywords : activation energy; admixtures; CaSO4.2H2O; crystallization, gypsum; reaction rate